2022
DOI: 10.3390/w14203322
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implementation for Water Resources Protection: Assessing Spatio-Temporal Trends of Results from Process-Based Outcomes of Resource-Directed Measures Projects in South Africa

Abstract: Governments are continuously developing strategies for policy implementation toward water resource protection. However, little is known about the practical application of such plans to test their effectiveness in policy practice. This study focused on resource-directed measures (RDMs) in South Africa to assess progress made on policy implementation for water resource protection. The study included document surveys and content analysis of the publicly available reports and documents sourced from state departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…The catchment was identified as Resource Unit 62 (RU62) within the delineated integrated unit of analysis UI of the UV-WMA [24]. The catchment was prioritised for water resource protection, and numerical limits for nitrate, phosphate, and electrical conductivity were prescribed and legalized through the government gazette [24]. This makes the BRC an ideal case study area for testing the feasibility of RDM operationalization.…”
Section: Study Area Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The catchment was identified as Resource Unit 62 (RU62) within the delineated integrated unit of analysis UI of the UV-WMA [24]. The catchment was prioritised for water resource protection, and numerical limits for nitrate, phosphate, and electrical conductivity were prescribed and legalized through the government gazette [24]. This makes the BRC an ideal case study area for testing the feasibility of RDM operationalization.…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Therefore, while water quality guidelines set numerical limits for various water uses, resource-directed measures (RDMs) such as RQOs set limits for a particular resource to protect its current conditions or improve them. In this regard, several studies on RDMs have been concluded in the country [24]. Results from such studies and projects involving resource-directed actions are reported in the official publications from the government.…”
Section: Introductionmentioning
confidence: 99%
“…In policy practice, in addition to formulating scientific and reasonable policies, the effectiveness of policy implementation is crucial [37]. Policy implementation is a key link in achieving policy goals and an important method for testing the scientific nature of policy formulation [38].…”
Section: H1mentioning
confidence: 99%
“…3, is aimed at reducing water pollution and eliminating hazardous substances in water. Since water resources are a key socioeconomic development resource, sustainable water resource management should be prioritized as a development cornerstone (Makanda et al 2022). The African Union Agenda 2063 further identi es unsustainable water resource management and pollution as barriers to improving quality of life and climate change resilience (African Union 2020; Gar as Royo et al 2022).…”
Section: Introductionmentioning
confidence: 99%